INSTAGRAM SEBAGAI AJANG MENUNJUKKAN EKSISTENSI DIRI PADA REMAJA DI KOTA DENPASAR - Kristina, Ruth; Zuryani, Nazrina; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
ABSTRACT This study attempted to examine the use of Instagram social media networks asqaqplaceqto show9the8self-existence of teenagers in Denpasar city. The>approach<usedXinXthisXstudyXis aXqualitativeXapproachAwithRdescriptiveYqualitative type research and sharpened by Rom Harreâ€™s self-theory. The results showed that Instagram is widely used to show the self-existence of teenagers in the city of Denpasar. The self-existence shown by teenagers, according to Rom HarrÃ©'s self-theory, is influenced by personal concepts and views about their self and identity as well as social constructions formed by social environment. Behavior in processing and uploading photos is strongly influenced by social factors such as aesthetic photo trends that show style and fashion, shopping, popular photo backgrounds or places, and so on. Keywords; teenagers behavior, instagram, self existence.